Structural, Morphological and Optical Characterization of X80Y10Cu10 and Y80X10Cu10 (X = Se, Y, Te) Chalcogenide Thin Films. (2018) - Chandra, Pramesh; Kumar Verma, Arvind; Shukla, R.K.; Srivastava, Anchal
Abstract: In the present study, results on the influence of interchanging Se and Te as major content (80%) on the structural, morphological and optical properties of copper doped ternary chalcogenide thin films Se80 Te10 Cu10 (Se-rich) and Te80 Se10 Cu10 (Te-rich) are reported. The films have been synthesized on glass substrates by thermal evaporation method. Bulk samples used for synthesizing the thin films have been prepared using melt quenching technique. The films have been characterized by XRD, FESEM, UV-Visible-NIR spectroscopy and Photoluminescence (PL) spectroscopy. Structural studies show amorphous and polycrystalline nature of the Se-rich and Te-rich films respectively. Surface morphological images show scattered grains in the Se-rich film whereas densely packed and similar sized grains are found in the Te-rich film. Transmission is much higher for the Se-rich film in the near infrared region. PL spectra recorded at two different excitation wavelengths – 380 nm and 450 nm – invariably show green emission for both the films. Yellow emission is also found at 450 nm excitation wavelength.